PLASTIK BIODEGRADABLE BERBAHAN AMPAS SINGKONG DAN POLIVINIL ASETAT - Asni, Nurul; Saleh, Djonaedi; Rahmawati, Nadia (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Cassava waste by product from tapioca flour. For reducing environmental pollution cassava waste be use biodegradable plastics by adding polivinil asetat as adhesive and glycerol as plastisizer. The aim of this research is for knowing physical characteristic of biodegradable plastic.Ratio betwen cassava west and polivinil asetat (wt%) are 9:1; 8:2;7:3;6:4. Tensile strength and elongation result from this research for 6:4 ratio’s are 0,1019 ± 0,339 MPa and 26,178%. Tensile strength and elongation for 9:1, ratio’s are 0,1659 ± 0,035 MPa and 22,386%. Key word : Cassava waste, Polivinil Asetat, Glycerol, Biodegradable plastics.